2019
DOI: 10.1155/2019/5364730
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Probiotic Supplement in Pregnant Women with Gestational Diabetes Mellitus: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Background. Previous studies showed that probiotics could improve glycemic control and attenuate some of the adverse effects of type 2 diabetes. However, whether the effects are generalizable to gestational diabetes mellitus (GDM) remains uncertain. Objective. We conducted a systematic review and meta-analysis to evaluate the effects of probiotic supplement in GDM. Method. PubMed, EMBASE, the Cochrane Library, and EBSCO were systematically searched for relevant literature published through January 2019. Random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 41 publications
5
31
0
4
Order By: Relevance
“…Probiotic administration resulted in a lower risk of offspring's hyperbilirubinemia. The authors also found the significant improvement of maternal glycemia, lipid profile, inflammation, and oxidative stress (186). In conclusion, inositols, ALA, vitamins, antioxidant supplementation, and multiple combinations of these compounds, associated with diet and lifestyle modifications, can be an important therapeutic option to manage PCOS and pregnancy-related complications.…”
Section: Expert Opinionmentioning
confidence: 84%
“…Probiotic administration resulted in a lower risk of offspring's hyperbilirubinemia. The authors also found the significant improvement of maternal glycemia, lipid profile, inflammation, and oxidative stress (186). In conclusion, inositols, ALA, vitamins, antioxidant supplementation, and multiple combinations of these compounds, associated with diet and lifestyle modifications, can be an important therapeutic option to manage PCOS and pregnancy-related complications.…”
Section: Expert Opinionmentioning
confidence: 84%
“…Mean treatment duration was approximately 9 weeks, ranging from 3 weeks of duration [ 67 ] to 26 weeks [ 56 ]. Women were treated with probiotic/synbiotic preparations during the third trimester of gestation in most of the trials (34 studies, 74%) [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 39 , 40 , 41 , 42 , 45 , 46 , 48 , 49 , 52 , 53 , 54 , 55 , 58 ,…”
Section: Resultsmentioning
confidence: 99%
“…Probiotic microorganisms have been used for a plethora of clinical indications such as lactose malabsorption, diarrhea, bowel syndrome, and infection, among others [ 6 ]. In pregnant women, the administration of these microorganisms has been proposed to alleviate gastrointestinal symptoms, improve glycemic control, reduce oxidative stress, and lower the incidence of asthma, atopic sensitization, and allergic disease in offspring, among other outcomes [ 7 , 8 , 9 ]. However, clinical evidence remains far from conclusive [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The probiotic supplementation did not increase the incidence of adverse perinatal outcomes 14,17 . Although the beneficial effects of probiotics on perinatal metabolic diseases and the mental disorders have been described, 8,18–22 the efficiency on the interactions of vaginal microbiome during the pregnancy is yet lacking. The previous study did not support that taking probiotics was significantly beneficial to pregnancy 16 .…”
Section: Discussionmentioning
confidence: 95%
“…Probiotics were known as the live microorganisms which exert health benefits to the host when administered in adequate amounts 7 . They are readily available for consumption as biological supplements or some components of food such as yogurt 7,8 . The probiotic supplementation has been claimed to be of more significance 7 and it has come to draw public attention.…”
Section: Introductionmentioning
confidence: 99%